Reversal of Sepsis‐Like Features of Neutrophils by Interleukin‐1 Blockade in Patients With Systemic‐Onset Juvenile Idiopathic Arthritis - Haar, Nienke M.; Tak, Tamar; Mokry, Michal; Scholman, Rianne C.; Meerding, Jenny M.; Jager, Wilco; Verwoerd, Anouk; Foell, Dirk; Vogl, Thomas; Roth, Johannes; Leliefeld, Pieter H. C.; Loosdregt, Jorg; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2018)
Objective Neutrophils are the most abundant innate immune cells in the blood, but little is known about their role in (acquired) chronic autoinflammatory diseases. This study was undertaken to investigate the role of neutrophils in systemic‐onset juvenile idiopathic arthritis (JIA), a prototypical multifactorial autoinflammatory disease that is characterized by arthritis and severe systemic inflammation. Methods Fifty patients with systemic‐onset JIA who were receiving treatment with recombinant interleukin‐1 receptor antagonist (rIL‐1Ra; anakinra) were analyzed at disease onset and during remission. RNA sequencing was performed on fluorescence‐activated cell–sorted neutrophils from 3 patients with active systemic‐onset JIA and 3 healthy controls. Expression of activation markers, apoptosis, production of reactive oxygen species (ROS), and degranulation of secretory vesicles from neutrophils were assessed by flow cytometry in serum samples from 17 patients with systemic‐onset JIA and 15 healthy controls. Results Neutrophil counts were markedly increased at disease onset, and this correlated with the levels of inflammatory mediators. The neutrophil counts normalized within days after the initiation of rIL‐1Ra therapy. RNA‐sequencing analysis revealed a substantial up‐regulation of inflammatory processes in neutrophils from patients with active systemic‐onset JIA, significantly overlapping with the transcriptome of sepsis. Correspondingly, neutrophils from patients with active systemic‐onset JIA displayed a primed phenotype that was characterized by increased ROS production, CD62L shedding, and secretory vesicle degranulation, which was reversed by rIL‐1Ra treatment in patients who had achieved clinical remission. Patients with a short disease duration had high neutrophil counts, more immature neutrophils, and a complete response to rIL‐1Ra, whereas patients with symptoms for >1 month had normal neutrophil counts and an unsatisfactory response to rIL‐1Ra. In vitro, rIL‐1Ra antagonized the priming effect of IL‐1β on neutrophils from healthy subjects. Conclusion These results strongly support the notion that neutrophils play an important role in systemic‐onset JIA, especially in the early inflammatory phase of the disease. The findings also demonstrate that neutrophil numbers and the inflammatory activity of systemic‐onset JIA are both susceptible to IL‐1 blockade.